Cybercrime and Law Enforcement Challenges in the Society 5.0 Era: A Modern Criminal Law Perspective - Hendri Khuan; Saptaning Ruju Paminto; Harly Clifford Jonas Salmon (Ipso Jure, 2025)
Abstract The Society 5.0 era brings deep integration between the physical and digital worlds, supported by technologies such as artificial intelligence (AI), Internet of Things (IoT), and big data. Behind these innovations, a new threat emerges in the form of cybercrime that is increasingly complex, anonymous, cross-border, and difficult to track. Cybercrime in this context does not only target individuals, but also strategic infrastructure, with the potential to disrupt social and economic stability. Indonesia's criminal law system, especially through the ITE Law, has not been fully able to keep up with this dynamic. Many of the provisions are multi-interpreted and focus on cracking down on content, rather than strategic digital crimes such as hacking, cyberespionage, or ransomware attacks. The limitations of digital forensics, the lack of international cooperation, and the lack of optimal digital proof regulations aggravate law enforcement. The descriptive normative legal research method in this study shows the urgency of criminal law reform that is more adaptive, collaborative, and technology-based. A new approach is needed that prioritizes the principles of digital justice, good governance, and cyber ethics to answer the challenges of transnational cybercrime. Without these reforms, Indonesia risks experiencing a justice deficit and is increasingly lagging behind in the legal response to digital crime in the Society 5.0 era. Therefore, the renewal of the criminal law paradigm is a necessity to maintain national digital security and sovereignty.